PERIODIC BOUNDARY VALUE PROBLEMS FOR HIGHER ORDER IMPULSIVE FUNCTIONAL DIFFERENTIAL EQUATIONS - Yuji LIU (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2009)
We prove existence results for the solutions of the periodic boundary valueproblem concerning the n-th order functional differential equation with impulses effects and the periodic boundary conditions. Our method is based upon the coincidence degree theory of Mawhin and some technicalinequalities. Examples are presented to illustrate the main results.